2017
DOI: 10.1016/j.bpj.2016.11.3204
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Active ICAM-4 on Normal and Sickle Cell Disease RBCs via AKAPs Is Revealed by AFM

Abstract: Human healthy (wild-type (WT)) and homozygous sickle (SS) red blood cells (RBCs) express a large number of surface receptors that mediate cell adhesion between RBCs, and between RBCs and white blood cells, platelets, and the endothelium. In sickle cell disease (SCD), abnormal adhesion of RBCs to endothelial cells is mediated by the intercellular adhesion molecule-4 (ICAM-4), which appears on the RBC membrane and binds to the endothelial αvβ3 integrin. This is a key factor in the initiation of vaso-occlusive ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 58 publications
(80 reference statements)
2
21
0
Order By: Relevance
“…We additionally corroborated this finding through the use of single‐molecule AFM (1821). An AFM‐based approach allows for the quantitative measurement of surface K Ca 2 channels in live neurons with nanometer resolution (20‐40 nm).…”
Section: Resultssupporting
confidence: 67%
“…We additionally corroborated this finding through the use of single‐molecule AFM (1821). An AFM‐based approach allows for the quantitative measurement of surface K Ca 2 channels in live neurons with nanometer resolution (20‐40 nm).…”
Section: Resultssupporting
confidence: 67%
“…Moreover, metal ions such as zinc (II) and copper (II) are implicated with increased aggregation of the Aβ peptide into toxic oligomers, accelerating the pathogenesis of Alzheimer's disease [22,23]. Thus, the AFM-based studies attempted to investigate whether the disruption of the cell-cell/ substrate adhesions affects the progression of these diseases [24][25][26][27][28].…”
Section: Ivyspringmentioning
confidence: 99%
“…where the expression of active adhesion receptors was measured (Maciaszek et al, 2012;Zhang et al, 2017). Because of this, we expect that the same level of wall shear stress will not have the same effect on all RBCs in terms of detachment from the substrate.…”
Section: Adhesion Assaymentioning
confidence: 99%
“…It has been shown that the adhesive behavior and viscoelastic response of SS-RBCs are important factors in vaso-occlusion (Evans et al, 1984). SS-RBC adhesion to specific proteins, such as human integrin α β v 3 , expressed on the endothelium has been implicated as part of the mechanism that triggers vaso-occlusive crises (Zennadi et al, 2004;Zhang et al, 2017). During a vaso-occlusive crisis adherent SS-RBCs in the vasculature obstruct other SS-RBCs due to their viscoelastic and mechanical properties (Hillery and Panepinto, 2004;Quinn et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation